Analysis of Natural Gas Network Development Policy for Households (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Based on data (ESDM, 2022), the realization of the construction of a natural gas network for households means that in 2021 there will only be 799,000 house connections (sambungan rumah/SR). This shows that the target of the National Energy General Plan (RUEN) cannot be fulfilled even by half by 2021. RUEN's target for the construction of natural gas networks in 2025 is 4.7 million house connections. Departing from these problems, researchers conducted an analysis of the natural gas network development policy for households. This research was conducted using the literature review method. The results of the study found that there were several obstacles to the implementation of natural gas development policies for households. These constraints are resources, communication, disposition, and bureaucratic structure. However, the most significant impediment is a lack of budgetary resources to complete the construction of natural gas networks for households.